Nourishing harmony: Exploring the role of nutrition in traditional chinese medicine - Varon, Adylle (Indonesian Nutrition Association, 2024)
Traditional Chinese Dietary Medicine (TCDM) has garnered increasing attention for its holistic approach to health and well-being, emphasizing the importance of balance and harmony within the body and its relationship with the environment. This subsection of Traditional Chinese medicine (TCM) integrates core principles such as Yin-Yang theory, Five Elements theory, and the concepts of Qi (vital energy) and Blood to provide a comprehensive framework for dietary recommendations.